2020
DOI: 10.3390/vehicles2020015
|View full text |Cite
|
Sign up to set email alerts
|

Powertrain Control for Hybrid-Electric Vehicles Using Supervised Machine Learning

Abstract: This paper presents a novel framework to enable automatic re-training of the supervisory powertrain control strategy for hybrid electric vehicles using supervised machine learning. The aim of re-training is to customize the control strategy to a user-specific driving behavior without human intervention. The framework is designed to update the control strategy at the end of a driving task. A combination of dynamic programming and supervised machine learning is used to train the control strategy. The trained con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Other similar approaches combining NN learning from optimisation results from DP or other control optimisation techniques were used by other authors as well for the control of on-road vehicles [83][84][85][86][87][88][89][90][91][92]. What is observed from this collection of studies on the topic is the ability of the networks to learn complex decision-making processes from system states and other measured variables and implement them in both simulation domains and in real systems.…”
Section: Supervised Learningmentioning
confidence: 99%
“…Other similar approaches combining NN learning from optimisation results from DP or other control optimisation techniques were used by other authors as well for the control of on-road vehicles [83][84][85][86][87][88][89][90][91][92]. What is observed from this collection of studies on the topic is the ability of the networks to learn complex decision-making processes from system states and other measured variables and implement them in both simulation domains and in real systems.…”
Section: Supervised Learningmentioning
confidence: 99%
“…In [8], an exhaustive chronological review of the most famous real-time capable control methods for (P)HEVs is reported. Starting from the 1990s, more and more sophisticated techniques have been developed, from very simple rule-based EMSs [8], passing through equivalent consumption minimization strategies (ECMS) [9,10] and dynamic programming (DP) [11] related optimizers, until the latest findings of model predictive control (MPC) [12] and learning algorithms [13,14]. Among the latter, Reinforcement Learning (RL) has started to be effectively exploited for control problems from 2015 onwards [8,15]; hence, it can be considered as an up-to-date approach.…”
Section: Introductionmentioning
confidence: 99%
“…The target fuel of future vehicles is hydrogen, which would either be used as the sole fuel [49,50] or as an additive to other fuels [51,52]. Energy management now plays an important role in hybrid or battery systems in the same way as with ICE [53][54][55]. Determining the characteristic ratios of different propulsion sources and whether their shape/path matches with the approximating functions is important for computing and modelling the performance of different vehicle powertrains [56,57].…”
mentioning
confidence: 99%